Identyfikacja kluczowego sektora lokalnej gospodarki jako czynnik rozwoju obszarów wiejskich - Karmowska, Grażyna; Sobczyk, Andrzej (Main Local Economy Sector Identification as a Development Factor for Rural Areas, 2006)
Observation and evaluation of state and changes reaching local economy needs a proper system. This systems should also act according to the dynamism of every and single economical process. The observation should include many areas of local activities and reach beyond economy. This complex system as a basis has highly developed tools (statistical analysis, query research, software) to convert data and huge amount of diverse and changing in time and space data.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 366-373